Nutrition stakeholders in India: Insights from a network and influence mapping exercise - Aberman, Noora-Lisa; Pradhan, Mamata; Cyriac, Shruthi; Singh, Kavita; Kadiyala, Suneetha; Menon, Purnima (International Food Policy Research Institute, 2013)
To better understand the landscape of and links among actors involved in influencing program and policy decisions in nutrition in India, a team from POSHAN conducted a stakeholder network mapping exercise. The team used Net-Map1; which is a participatory interview tool that combines social network analysis, stakeholder mapping, and power mapping. The tool is intended to help visualize and understand situations in which many different actors influence particular outcomes. Net-Map allows stakeholders to examine not only the formal interactions in a network, but also the informal interactions that cannot be understood by merely studying documents concerning the formal policymaking procedures.